(untitled) (Journal of Forest and Livelihood, 2003)
This paper describes an approach to developing and using process indicators of the institutional development of Forest User Groups (FUGs) in Nepal. Assessments of FUGs were carried out with forest users, on the basis of indicators identified by the users themselves. The approach is helpful in distinguishing patterns of development in the institutional diversity of FUGs, and highlighting support they require. Post-formation support to FUGs is perhaps the most pressing issue of community forestry. So far, it has tended to be oriented to technical forestry and yield-regulation. If community forestry is to genuinely reflect local people’s priorities then there is a need to move towards a more holistic and dynamic approach: including supporting regular self-assessment of FUGs’ changing needs, specific support in conflict management, easier amendment of forest management plans, and ‘entrepreneurial’ support.